Die belydenisuitspraak Kolossense 1: 13-20: Eenheid, struktuur en funksie - Roberts, J. H. (Hervormde teologiese studies, 1997)
The confessional statement Colossians 1:13-20: Unity, structure and function. Scholarly work has concentrated much effort on Colossians 1:15-20 as an early Christian hymn. In discussions with Botha (1986; 1989) and Van der Watt (1988), an attempt has been made here to prove the unity of 1 :13-20 as a confessional statement, and to determine its structural coherence and progression. The letter's macro structure is utilized to pinpoint the pericope's locality in the letter since this has bearing on the function it fulfills. The analysis of its structural composition is an attempt to help clarify my position on various details and understanding of its meaning. In view of the positions taken and of a discussion of the letter's context and its communicative thrust, the function of the confessional statement is considered to be its role of grounding the community's faith in the totally sufficient salvation by God in Christ thus opening the way for the warning against being misled on a way other than that of Christ and to hold onto him as head, which signals the communicative thrust of the letter.